Effects of Titanium Dioxide Nanoparticles on Porcine Prepubertal Sertoli Cells: An “In Vitro” Study - Mancuso, Francesca; Arato, Iva; Di Michele, Alessandro; Antognelli, Cinzia; Angelini, Luca; Bellucci, Catia; Lilli, Cinzia; Boncompagni, Simona; Fusella, Aurora; Bartolini, Desirée; Russo, Carla; Moretti, Massimo; et al. (Frontiers in Endocrinology, 2022)
The increasing use of nanomaterials in a variety of industrial, commercial, medical products and their environmental spreading has raised concerns regarding their potential toxicity on human health. Titanium dioxide nanoparticles (TiO2 NPs) represent one of the most commonly used nanoparticles. Emerging evidence suggested that exposure to TiO2 NPs induced reproductive toxicity in male animals. In this in vitro study, porcine pre-pubertal SCs have undergone acute (24 hours) and chronic (from 1 up to 3 weeks) exposures at both sub-toxic (5g/ml) and toxic (100 g/ml) doses of TiO2 NPs. After performing synthesis and characterization of nanoparticles, we focused on SCs morphological/ultrastructural analysis, apoptosis and functionality (AMH, inhibin B), ROS production and oxidative DNA damage, gene expression of antioxidant enzymes, proinflammatory/immunomodulatory cytokines and, MAPK kinase signaling pathway. We found that 5 g/ml TiO2 NPs did not induce substantial morphological changes overtime but ultrastructural alterations appeared at the third week. Conversely SCs exposed to 100 g/ml TiO2 NPs throughout the whole experiment showed morphological and ultrastructural modifications. TiO2 NPs exposure, at each concentration, induced the activation of caspase-3 at the first and second week. AMH and inhibin B gene expression significantly decreased up to the third week at both concentrations of nanoparticles. The toxic dose of TiO2 NPs induced a marked increase of intracellular ROS and DNA damage at all exposure times. At both concentrations, the increased gene expression of antioxidant enzymes such as SOD, HO-1 was observed whereas, at the toxic dose, a clear pro-inflammatory stress was evaluated along with the steady increase in the gene expression of IL-1 and IL-6. At both concentrations, an increased phosphorylation ratio of p-ERK1/2 was observed up to the second week followed by the increased phosphorylation ratio of p-NF-kB in the chronic exposure. Although in vitro, this pilot study highlights the adverse effects even of sub-toxic dose of TiO2 NPs on porcine SCs functionality and viability and, more importantly, set the basis for further in vivo studies, especially in chronic exposure at sub-toxic dose of TiO2 NPs, a condition closer to the human exposure to this nano-agent.